Assessment of adequately iodised salt consumption in Telangana state, India - Mathur, Neeta; Pattnaik, Snigdha; Sayed, Saba; Das, B. N. (International Journal Of Community Medicine And Public Health, 2018)
Background: Salt used in the household is the most common way for iodine fortification to prevent the public health concerns of iodine deficiency disorders. The objective of the study was to assess household coverage with adequately iodized salt in Telangana State, India. Methods: Secondary data published in the District Level Household and Facility Survey-4 is analyzed. Results: Overall, 55.7 percent of the households were using cooking salt which was iodized at the recommended level of 15 ppm or more. Around 60.8 percent of households in urban areas used salt with 15 ppm or more iodine content compared with 51.9 percent of households in rural areas though the difference was not significant. Conclusions: The coverage of adequately iodized salt in the state was below the national average. To further expand the coverage of adequately iodized salt, researchers and policy makers should take action.